Post harvest management of black mould rot of onion - V. SHANMUGAM*, R. SRINIVASAN and (Indian Phytopathology, 2006)
Aspergillus niger was found to be predominantly associated with black mould rot of onion during storage. Onion bulbs cured by wind row method and stored by hanging method exhibited reduced disease incidence. Among the fungicides, carbendazim at 0. 1% concentration was found to be most effective when applied either as foliar spray in the standing crop or as a post-harvest dip. However, double spray was found to be better than single spray. In addition, post-harvest fumigation of onion bulbs with sulphur dioxide for four hours or dipping the bulbs in acetic acid at higher concentration (0.4 %) markedly reduced the disease incidence.